Effect of Self Acceptance Parent for Early Childhood Confidence in TK Negeri Pembina Kabupaten Demak - Ariyati, Dea Qori; Astuti, Henny Puji (Universitas Negeri Semarang, 2017)
Acceptance Parents and Early Childhood Confidence are the two things are related. Acceptance of parents it's important to give effect to the confidence of early childhood. Acceptance of parents is a psychological effect and behavior of parents in their children such as affection, attachment, care, support and parenting, where parents can feel and express affection to their children. This affects the confidence of early childhood because it is associated with psychological factors or external factors that may impact the child. This study used quantitative research methods. The population in this study were young children who were in kindergarten group B in District Demak. Samples were taken using simple random sampling technique total of 57 children who were in kindergarten Negeri Pembina, Pucanggading Jalan Raya, Batursari, Mranggen, Demak. The technique of collecting data using a scale that refers to a Likert scale. Test assumptions made using normality test and linieritas.Uji hypothesis using simple linear regression analysis. Results of research on the acceptability of the confidence of parents to early childhood with simple linear regression analysis showed that there is an influence of 30.9% against early childhood confidence. The conclusion from this study is the acceptance of the parents to contribute to early childhood confidence of 30.9% and the rest influenced by other factors.